1997
DOI: 10.1055/s-2007-979035
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Contributing to the Pancreatic β-Cell Phenotype

Abstract: Insulin promoter factor-1 (IPF1) (renamed to pancreatic-duodenal homeobox factor-1, PDX1) was originally cloned and characterized as an islet beta-cell specific insulin gene transcription factor (1) and later shown to be essential for the formation of the mature pancreas (2, 3). In the adult normal pancreas PDX1 is almost exclusively expressed in the beta-cell compartment and generally absent from the alpha-cell while it is widely expressed in the pancreatic epithelium during development. Using pluripotent rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Using this characteristic of DTZ, we identified insulin-producing cells in EB outgrowths derived from mouse ES cells as well as cellular clusters. We then analyzed the characteristic features of these DTZ-stained clusters by immunohistochemistry for insulin production and by reverse transcriptase-polymerase chain reaction (RT-PCR) for gene expression of the pancreatic β-cell markers, including proinsulin 1, proinsulin 2, pancreatic transcription factor pancreatic-duodenal homeobox 1 (PDX1) [32,33], glucose transporter-2 (GLUT2) [34,35], and islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) [36,37]. We also examined insulin secretion using an enzyme-linked immunoassay (ELISA).…”
Section: ® Original Articlementioning
confidence: 99%
“…Using this characteristic of DTZ, we identified insulin-producing cells in EB outgrowths derived from mouse ES cells as well as cellular clusters. We then analyzed the characteristic features of these DTZ-stained clusters by immunohistochemistry for insulin production and by reverse transcriptase-polymerase chain reaction (RT-PCR) for gene expression of the pancreatic β-cell markers, including proinsulin 1, proinsulin 2, pancreatic transcription factor pancreatic-duodenal homeobox 1 (PDX1) [32,33], glucose transporter-2 (GLUT2) [34,35], and islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) [36,37]. We also examined insulin secretion using an enzyme-linked immunoassay (ELISA).…”
Section: ® Original Articlementioning
confidence: 99%
“…Induction of these nonspecific proteins has been previously described (7,12,14,15); it is now shown that they occur independently of cytotoxic effects. Suppression of transcription factor PDX-1 is expected to result in lower expression of -c e l l -s p e c i fic genes, such as insulin, I A P P, GLUT2, and glucokinase (31)(32)(33)(34). These data are consistent with the concept that IL-1 can shift the functional state of -cells to that of a glucose-unresponsive population, which explains the loss of their characteristic property, namely the production of insulin in response to glucose (6).…”
Section: Interleukin-1 -Induced Protection Of -Cellsmentioning
confidence: 99%
“…Recently, the study of the transcriptional regulation of the insulin gene has led to the identification of several ␤ cell/islet transcription factors that are important for the development of the endocrine pancreas, the tissue-specific expression of key ␤ cell genes and maintenance of ␤ cell differentiation (9,10). In islets of diabetic animals and in long term culture of immortalized insulin-secreting cells, chronic exposure to high glucose can result in loss of insulin gene expression (11,12).…”
mentioning
confidence: 99%